Transmission Electron Microscopy: Novel Application of Established Technique in Characterization of Nanoparticles as Drug Delivery Systems - Petrushevska, Marija; Pavlovska, Kristina; Laskova, Jovanka; Zdravkovski, Panche; Glavas Dodov, Marija (Македонска академија на науките и уметностите, Одделение за медицински науки = Macedonian Academy of Sciences and Arts, Section of Medical Sciences/Sciendo, 2019)
Nanotechnology presents a modern field of science that in the last twenty-five years plays a dominant role in the biomedicine. Different analytical methods are used for evaluation of the physico-chemical properties of nanoparticles including chromatography, electrophoresis, X-ray scattering, spectroscopy, mass spectrometry, zeta potential measurement and microscopy on which this article will focus. Herein, we present novel application of the long-established TEM technique that is focused on characterization and evaluation of various nanoparticles in development of drug delivery systems. Transmission electron microscopy images were taken of samples from native nanoparticles, nanoparticles labeled using stannous chloride labeling procedure, inorganic silica nanoparticles loaded with budesonide and native micelles and micelles carrier of anticancer drug camptothecin. In the case of radiolabeled nanoparticles, beside for nanoparticle characterization, TEM technique was used to confirm the stability of the nanoparticles after radiolabeling. Furthermore, the porous structure of hybrid silica particles loaded with budesonide was examined under TEM. Transmission electron microscopy technique offers exceptional benefits for nanoparticle characterization. Additionally, the necessity of ultrastructural analysis demonstrates the potential of TEM in the field of nanomedicine. Hence, the long-established and well-known TEM has been only partially exploited and offer researchers very detailed images of specimens at microscopic and nano scale.